Collateral pledgeability and asset manager portfolio choices during redemption waves - Fauvrelle, Thiago,Riedel, Max,Skrutkowski, Mathias (ESM, 2023)
This paper studies whether Eurosystem collateral eligibility played a role in the portfolio choices of euro area asset managers during the
10.2852/99948
Keywords: Graue Literatur; Investment funds; dash-for-cash; corporate bonds; Eurosystem collateral eligibility; euro area; Eurosystem; European Investment Fund; bond; European Central Bank; money-market liquidity